2022
DOI: 10.1101/2022.08.05.22278366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Super-resolution imaging pinpoints ultrastructural changes at the node of Ranvier in patients with polyneuropathy

Abstract: The peripheral node of Ranvier is the key element in saltatory conduction along myelinated axons, but its ultrastructural protein arrangement and interactions remain elusive in humans. To assess both physiological protein arrangement and pathological ultrastructural changes at the paranodal region of the node of Ranvier, we implement the super resolution microscopy method direct Stochastic Optical Reconstruction Microscopy (dSTORM) assisted by high-content confocal microscopy on nerve biopsies of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 111 publications
(256 reference statements)
1
1
0
Order By: Relevance
“…However, we do not think that the claim for neurofilament light chain (NfL) being a marker of just central nervous system damage is justified. Numerous studies on peripheral nerve disease, most notably Guillain-Barré syndrome (GBS), and similar acute neuropathies, have shown that nerve-root and blood-nerve barrier disruption are important determinators of serum NfL levels [1,2]. The negative correlation with sural sensory nerve action potential amplitude, even in our cohort with small fiber neuropathy (SFN), is indeed intriguing, as it has been shown in other neuropathies [2].…”
supporting
confidence: 70%
See 1 more Smart Citation
“…However, we do not think that the claim for neurofilament light chain (NfL) being a marker of just central nervous system damage is justified. Numerous studies on peripheral nerve disease, most notably Guillain-Barré syndrome (GBS), and similar acute neuropathies, have shown that nerve-root and blood-nerve barrier disruption are important determinators of serum NfL levels [1,2]. The negative correlation with sural sensory nerve action potential amplitude, even in our cohort with small fiber neuropathy (SFN), is indeed intriguing, as it has been shown in other neuropathies [2].…”
supporting
confidence: 70%
“…It would also be very interesting to assess the dynamics of NfL and peripherin blood levels during and after nerve damage: How high is the increase and how long does it last? We and others have shown that NfL levels in peripheral neuropathies are higher in the acute stage and diminish over time, even if axonal damage is still present [1,4]. Studies of different peripheral nerve diseases (e.g., GBS, chronic inflammatory demyelinating polyneuropathy, SFN, trauma) will be needed to obtain a clear picture.…”
mentioning
confidence: 98%
“…In conclusion, using intravital imaging, we have characterised NoR morphologies in FMNs and SMNs, identified accumulations of signalling endosomes and mitochondria at the distal NoR, and determined the axonal transport dynamics of both organelles through the NoR. Finally, this work has clear implications for the peripheral nervous system and its numerous disorders (e.g., motor neuron diseases, multiple sclerosis) (Appeltshauser et al, 2023; Eshed-Eisenbach et al, 2023), and suggests that both the internodal and nodal transport modalities should be monitored in neuronal models of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 81%